2015
DOI: 10.1007/s11042-015-2955-0
|View full text |Cite
|
Sign up to set email alerts
|

Training emergency responders through augmented reality mobile interfaces

Abstract: In the domain of emergency management, in addition to the constant technical skill-upgrade required by the nature of the humanitarian context, the importance of an appropriate training is widely recognized. In particular, giving responders information technology skills so that they are well prepared to address health, security and managerial concerns represents a key factor by which the goal of an efficient and effective humanitarian emergency response can be pursued. In this paper we propose the adoption of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 7 publications
0
26
0
1
Order By: Relevance
“…They concluded that technology-controlled sensory augmentation could impact human perception and improve the execution of those actions but depending on the targeted population and the amount of augmentation, can have negative effects like overloading the user with too much information. Sebillo et al have used AR technologies to improve training of workers in the emergency domains [5]. Emergency domains have certainly benefited from the usage of information technologies regarding improving the emergency control processes by providing tools which support decision making in critical situations.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that technology-controlled sensory augmentation could impact human perception and improve the execution of those actions but depending on the targeted population and the amount of augmentation, can have negative effects like overloading the user with too much information. Sebillo et al have used AR technologies to improve training of workers in the emergency domains [5]. Emergency domains have certainly benefited from the usage of information technologies regarding improving the emergency control processes by providing tools which support decision making in critical situations.…”
Section: Introductionmentioning
confidence: 99%
“…Pembuatan (Smart Augmented Field for Emergency) untuk tim penyelamat dan operator yang terlibat dalam misi penyelamatan yang menggunakan teknologi Augmented reality [10]. Penggunaan Augmented reality untuk latihan yang memberikan keterampilan teknologi informasi kepada responden sehingga mereka siap menghadapi masalah kesehatan, keamanan, dan manajerial pada saat tanggap darurat [11].…”
Section: Pendahuluanunclassified
“…MR also aids skill training such as manual assembly with an intuitively enhanced bare-hand MR interface, which can provide suitable and appropriate guidance, so users can perform tasks more quickly and accurately (Wang et al 2016a). Systems for training emergency management (Sebillo et al 2016), and endourologic skills (Sweet 2017) meet the needs for training and assessing particular skills. An increase in task completion time is a tradeoff which might be worth investigating to decrease the mental demand of industrial robot programmers (Stadler et al 2016), or to avoid shifts in focus and enable the fine-tuning execution of surgical tasks (Andersen et al 2016).…”
Section: Educationmentioning
confidence: 99%